Spectroscopic approach of the association of heparin and its contaminant and related polysaccharides with polymers used in electrokinetic chromatography - Flor, Sabrina Andrea (2012)
Heparin (Hep) is a linear sulfated polysaccharide used in clinical treatment of tromboembolic diseases. In 2008, contaminated batches of Hep appeared in the pharmaceutical market. The contaminant was identified as an over sulfated form of chondroitin sulfate (oversulfated chondroitin sulfate, OSCS). Different analytical methods have been developed to identify and quantify OSCS and other impurities expressed as dermatan sulfate from Hep. In this sense, we have developed a capillary electrophoretic method based on the use of a mixture of polymers such as polymeric b-cyclodextrin and poloxamine. As a result of this combination, not only the resolution of Hep from its impurities and contaminant was obtained but the sensitivity was extremely improved. The association of Hep and its related polysaccharides with the polymers was characterized by spectroscopic techniques as ultraviolet (UV) and infrared (IR). The results suggest that the interaction between polysaccharides and polymers would principally be through the sulfate groups of polysaccharides.b-cyclodextrin and poloxamine. As a result of this combination, not only the resolution of Hep from its impurities and contaminant was obtained but the sensitivity was extremely improved. The association of Hep and its related polysaccharides with the polymers was characterized by spectroscopic techniques as ultraviolet (UV) and infrared (IR). The results suggest that the interaction between polysaccharides and polymers would principally be through the sulfate groups of polysaccharides.